2002
DOI: 10.1126/science.1071489
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Loss of a Neoplastic Phenotype by Brief Inactivation of MYC

Abstract: Pharmacological inactivation of oncogenes is being investigated as a possible therapeutic strategy for cancer. One potential drawback is that cessation of such therapy may allow reactivation of the oncogene and tumor regrowth. We used a conditional transgenic mouse model for MYC-induced tumorigenesis to demonstrate that brief inactivation of MYC results in the sustained regression of tumors and the differentiation of osteogenic sarcoma cells into mature osteocytes. Subsequent reactivation of MYC did not restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
479
5
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 614 publications
(512 citation statements)
references
References 21 publications
26
479
5
2
Order By: Relevance
“…The contradiction between the above findings may be explained in view of previous studies suggesting that the effect of a single gene may differ according to the genetic and cellular context. For example, c-MYC can induce both cell proliferation and apoptosis (Evan et al, 1992;Jain et al, 2002;Pelengaris et al, 2002). Another example was given by Serrano et al (1997), who showed that the oncogene ras, known for its ability to transform immortal rodent cells to a tumourigenic state, can provoke premature cell senescence in primary human and rodent cells.…”
Section: Discussionmentioning
confidence: 99%
“…The contradiction between the above findings may be explained in view of previous studies suggesting that the effect of a single gene may differ according to the genetic and cellular context. For example, c-MYC can induce both cell proliferation and apoptosis (Evan et al, 1992;Jain et al, 2002;Pelengaris et al, 2002). Another example was given by Serrano et al (1997), who showed that the oncogene ras, known for its ability to transform immortal rodent cells to a tumourigenic state, can provoke premature cell senescence in primary human and rodent cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, targeting Wnt/β-catenin pathway that is responsible for self-renewal can be a potential therapeutics strategy (Woodward et al, 2007). Although mutation of β-catenin may not commonly occurred in human breast cancers, various studies showed the role of Wnt signaling pathway in pathogenesis of breast cancer (Lin et al, 2000;Jain et al, 2002;Wong et al, 2002;Klopocki et al, 2004) suggesting a link between Wnt signaling and DNA damage response in epithelial cells (Ayyanan et al, 2006).…”
Section: 2789 Application Of Stem Cells In Targeted Therapy Of Breasmentioning
confidence: 99%
“…Weinstein (2000) wrote that even if the development of microarray methods and proteomics expands our ability to assess complex profiles of gene expression in cancer cells, these methods do not provide the dynamic view of the actual circuitry of these cells. Recently, however, direct experimental evidence of an epigenetic mechanism has been reported: the MYC oncogene is frequently overexpressed in cancer cells and its brief inactivation in an osteogenic sarcoma cell line appeared to cause epigenetic changes that rendered the cells insensitive to MYCinduced tumorigenesis (Jain et al, 2002).…”
Section: Resultsmentioning
confidence: 99%